Communicating About Affirmative Consent: How the Threat of Punishment Affects Policy Support and Gender Stereotypes. Issue 21 (November 2018) - Tinkler, Justine E.; Clay-Warner, Jody; Alinor, Malissa
Colleges are increasingly adopting "affirmative consent" policies, which require students to obtain conscious and voluntary consent at each stage of sexual activity. Although this is an important step forward in violence prevention, very little is known about how best to present the policies to students. This is important, as research on sexual harassment policy training finds that training can reinforce traditional gender beliefs, which undermines policy goals. Building on this literature, we argue that affirmative consent policy trainings emphasizing punishment will increase support for affirmative consent but will reinforce traditional gender beliefs. We tested our predictions with an experiment in which we randomly assigned undergraduate participants to one of three conditions where they read an excerpt of (a) an affirmative consent policy that emphasized the threat of punishment, (b) an affirmative consent policy that emphasized a normative/moral message, or (c) an ergonomic workstation policy that served as our control condition. We found that punishment framing increased men's support for the policy, had no effect on their likelihood to comply, and increased their perception that "most people" hold men to be more powerful than women. For women, the punishment and normative framings increased support equally, but the normative framing actually decreased likelihood to comply. The policy conditions had no effect on women's gender beliefs. The results suggest that while an emphasis on punishment can help legitimate nonconsensual sex as a social problem, it will not necessarily increase college students' compliance with affirmative consent, and runs the risk of activating essentialist stereotypes about gender difference. As the issue of campus sexual assault becomes increasingly politicized and contested, our findings highlight the need for more research.